Análise das propriedades mecânicas e tribológicas do aço AISI H13 submetido ao tratamento criogênico e nitretação a plasma - Nieswald, Romulo (2023)
Hot work tool steels are widely used in the manufacture of injection molds, dies and forging tools due to their ability to maintain their mechanical properties when exposed to high temperature working conditions. In view of this, in order to further improve the mechanical and tribological properties of steels, cryogenic and plasma nitriding treatments combined with quenching and tempering present themselves as an excellent alternative to increase tool life. Based on that, the present work aims to evaluate and compare the performance of the mechanical and tribological properties of H13 tool steel submitted to conventional heat treatments in conjunction with cryogenic and plasma nitriding, varying the sequence in which the treatments are performed. The methodology used to carry out the work was experimental research, in which the sequence of treatments was varied. The austenitizing temperature used on the samples was 1030°C and cooled in oil, tempering was done at 500°C for 2 hours, cryogenics reached -180°C for 24 hours with a cooling and heating ramp of 0.5°C/min, and plasma nitriding was done at 440°C for 90 minutes using a gas mixture of N2 and H2. After that, mechanical tests and microstructural analysis were performed to evaluate the changes in the mechanical and tribological properties of the steel. The results obtained show that the application of cryogenics combined with plasma nitriding at the end of the treatment cycles contributes significantly to the increase in wear resistance, microhardness and compressive residual stresses, however reduced impact toughness when compared to the T/2R route. For hardness the results obtained show that plasma nitriding has no significant influence on the hardness of the core material, but rather on the surface layer. For the cryogenic and plasma nitriding routes it is observed that there was a refinement of the microstructure when compared to the T/2R route. In addition, it can be seen that the routes in which tempering was performed after nitriding presented the white layer, which is formed iron nitrides that provide a hard and brittle surface for the material.